EUTROPHICATION IN THE LOWER COASTAL BASIN OF THE JAMAPA RIVER IN VERACRUZ, MEXICO - Castañeda-Chávez, María del Refugio; Sosa-Villalobos, Cinthya A; Amaro-Espejo, Isabel A; Galaviz-Villa, Itzel; Lango-Reynoso, Fabiola (International Journal of Research -GRANTHAALAYAH, 2017)
The aim of this study was to determine parameters of dissolved oxygen, temperature and nitrogen in the coastal basin of the Jamapa River as indicators of eutrophication. Six sampling sites were selected in the lower basin, where samples were collected in triplicate in each site, during three seasons; north winds, dry and rainy. Results of the research, analyzed using the Minitab statistical program, were: site 2 showing the maximum value of dissolved oxygen with 5.83 mg/L; site 5 with the maximum temperature value of 30.3 ºC, during the dry season. Whereas, maximum mean values of total nitrogen were at site 2 (4.596 mg/L) and site 5 (4.281 mg/L). Coastal basins can change markedly the nitrogen concentration with respect to weather and environmental conditions. As well as, reduced forms of nitrogen cause alterations in dissolved oxygen and the increase in water temperature, along with high concentrations of nutrients.